A real time vein detection system - Ahmed, Kazi Istiaque; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (Indonesian Journal of Electrical Engineering and Computer Science ( IAES), 2018)
Blood veins detection process can be cumbersome for nurses and medical practioners when it comes to special overweight type of patients. This simple routine procedure can lead the process into an extreme calamity for these patients. In this paper, we emphasized on a process for the detection of the vein in real time using the consecrations of Matlab to prevent or at least reduce the number of inescapable calamity for patients during the infusion of a needle by phlebotomy or doctor in everyday lives. Hemoglobin of the blood tissues engrossed the Near Infrared (NIR) illuminated light and Night vision camera is used to capture the scene and enhance the vein pattern clearly using Contrast Limited Adaptive Histogram Equalization (CLAHE) method. This simple approach can successfully also lead to localizing bleeding spots, clots from stroke … etc among other things.